A case of cervical clear cell carcinoma with serous component. Issue 7 (18th April 2021) - Ebisawa, Keiko; Sugiyama, Takahiro; Itami, Makiko; Maru, Yoshiaki; Hippo, Yoshitaka; Tanaka, Naotake
Abstract: Cervical clear cell carcinoma (CCCC) is rare. This report describes the case of CCCC with a serous component. A 22‐year‐old woman presented with vaginal bleeding. A cervical tumor was discovered: pelvic magnetic resonance imaging revealed a tumor measuring 46 mm. Radical hysterectomy was performed based on the diagnosis of stage IB2 cervical cancer. After histological examination of the specimen revealed a coexisting invasive clear cell carcinoma (95%) and serous carcinoma (5%), five cycles of nedaplatin and irinotecan therapy were administered as postoperative adjuvant chemotherapy. Local recurrence in the vaginal vault was observed at 7 months after surgery. Radiation therapy and chemotherapy were administered. The patient is alive without evidence of recurrence at 26 months after surgery.